Tricharina tophiseda—a new species from Croatia, with a revision of T. japonica (Pyronemataceae, Pezizales) - Kušan, Ivana; Matočec, Neven; Mešić, Armin; Tkalčec, Zdenko (Phytotaxa, 2015)
A new species, Tricharina tophiseda, is described in detail on the basis of both teleomorph and anamorph states. A comparative study of the most similar species, T. japonica, is provided by re-examination of the holotype and recently collected European material. Highly diverse characters of species in Tricharina and closely related genera demonstrate concurrence with polyphyly ascertained by a number of previous phylogenetic studies.